Mental State Attribution and Body Configuration in Women - Bremser, Jennifer; Gallup, Gordon (Frontiers in Evolutionary Neuroscience, 2012)
Body configuration is a sexually dimorphic trait. In humans, men tend to have high shoulder-to-hip ratios. Women in contrast, often have low waist-to hip ratios (WHR); i.e., narrow waists and broad hips that approximate an hour-glass configuration. Women with low WHR’s are rated as more attractive, healthier, and more fertile. They also tend to have more attractive voices, lose their virginity sooner, and have more sex partners. WHR has also been linked with general cognitive performance. In the present study we expand upon previous research examining the role of WHR in cognition. We hypothesized that more feminine body types, as indexed by a low WHR, would be associated with cognitive measures of the female “brain type,” such as mental state attribution and empathy because both may depend upon the activational effects of estrogens at puberty. We found that women with low waist-to-hip ratios excel at identifying emotional states of other people and show a cognitive style that favors empathizing over systemzing. We suggest this relationship may be a byproduct of greater gluteofemoral fat stores which are high in the essential fatty acids needed to support brain development and cellular functioning. It is interesting to note that our findings suggest lower WHR females, who are more likely to be targeted for dishonest courtship, may be better at identifying disingenuous claims of commitment.